Design and Construction of an Electric Motor. - Twinamasiko, Julius (Kabale University, 2024)
The main aim of this project was to construct and design a DC motor using locally available materials, providing a hands-on learning experience in the fundamental principles of electromagnetic induction and energy conversion. It was made of two magnets, wood, nails, payan, insulated copper wire, soft board, cello tape, polythene, hammer, saw, batteries, and plastic lid to design a simple DC motor therefore this project promotes innovation, creativity, and hands-on learning in physics and engineering education, making it a teaching and learning aid for electromagnetism.